DETECTING FRAUDULENT OF FINANCIAL STATEMENTS USING FRAUD S.C.O.R.E MODEL AND FINANCIAL DISTRESS - Andrew Andrew; Candy Candy; Robin Robin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The problem of fraud in financial statements is a global problem that has crossed borders of time and country. This research was created to prevent fraud by detecting financial statements listed on the Indonesia Stock Exchange (IDX). The fraud detection tools used in this research are F-S.C.O.R.E and Financial Distress. S.C.O.R.E stands for Stimulus, Capability, Opportunity, Rationalization, and Ego, which are supporting variables in detecting fraud. The research results show that Stimulus, Capability, and Financial Distress effectively detect fraud. Fraud detection in the research concluded that companies that have strong indications of committing fraud are companies categorized in industrials in the IDX Industrial Classification.